(untitled) (Journal of the College of Basic Education, 2022)
This work involves studying the corrosion behavior of some metals and alloys in condensed synthetic automotive solution (CSAS) at room temperature by Potentiostat at scan rate 3 mV.sec-1. The results show that stainless steel and copper are more stable than other materials (Al, Brass) in CSAS because the chromium oxide which formed on Steel surface and cupric oxide which formed on the Cu surface respectively. While brass may be attacked by aggressive ions and selective leaching can occur. Aluminium produce instable oxide layer compared with chromium and cupric oxides.